Fluorescent Properties of Hymecromone and Fluorimetric Analysis of Hymecromone in Compound Dantong Capsule. (4th December 2013) - Zhi, Huanhuan; Wang, Jingdan; Wang, Shujing; Wei, Yongju
Abstract : Fluorescence spectra of hymecromone (4MU) aqueous solutions are investigated at different pHs. Two fluorescent species of 4MU, neutral molecular form and anion form, are considered to be the main fluorescent forms. Quantum yields of the two forms are measured to be 0.74 at pH 5.98 and 0.95 at pH 9.75, respectively. The ionization constant of 7-hydroxyl proton of 4MU is determined to be p K a = 7.85 ± 0.03 by a pH-fluorescence method. Addition of methanol into 4MU aqueous solution leads to a blue shift of maximum emission wavelength from 445 nm to 380 nm, and a decrease in fluorescence intensity. 3D fluorescence spectra of Chinese patent drug Compound Dantong Capsule (CDC) and its four component herbal drugs are also investigated. Based on their fluorescent properties, a novel fluorimetric method is proposed for the selective determination of 4MU in CDC without preseparation. The new method is suitable for the routine quality evaluation of CDC.